Efforts of Class IIA Pekanbaru Women’s Penitentiary in Fulfilling the Rights of Inmates to Interact with Family in the Covid-19 Pandemic (Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2023)
Most of the female prisoners in Pekanbaru Class IIA Women’s Penitentiary have children and families, but while having their sentences, they can’t interact with their children or families as usual. Most of them are mothers. Mothers play an important role in children’s development. The method used in this research is a qualitative method to analyze about how is the efforts of Pekanbaru woman’s penitentiary in optimizing the provision of inmates’ rights by interacting with family during covid-19 pandemic. The results of this study are the efforts of Pekanbaru Class IIA Women’s Penitentiary on granting women’s right is not optimal, which is it is the same as in ordinary penitentiary. There is no special treatment for women in penitentiary even though the interaction with their families, especially their children is very important, considering the children will still need a mother figure. The conclusion of this research is women in penitentiary have a minimum interaction with their families, especially children, and it has the potential to cause children to commit deviate behavior. Based on social bond theory, there are four elements that influence children’s behavior, if any of these elements are not fulfilled then the children will deviate. The children will tend to have no attachment to their parents, especially mothers while the mother is in a penitentiary or prison, and it will cause children to commit delinquency